2011
DOI: 10.1021/nn1033357
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Levers Enabling Independent Control of Phase, Size, and Morphology in Nickel Phosphide Nanoparticles

Abstract: Simultaneous control of phase, size, and morphology in nanoscale nickel phosphides is reported. Phase-pure samples of discrete nanoparticles of Ni12P5 and Ni2P in hollow and solid morphologies can be prepared in a range of sizes (10-32 nm) by tuning key interdependent synthetic levers (P:Ni precursor ratio, temperature, time, oleylamine quantity). Size and morphology are controlled by the P:Ni ratio in the synthesis of the precursor particles, with large, hollow particles formed at low P:Ni and small, solid pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
235
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(255 citation statements)
references
References 32 publications
11
235
1
Order By: Relevance
“…Compared with other samples, the diffraction peaks of Ni 2 P-528 around 38.4 • , 41.7 • , 46.9 • and 48.9 • corresponding to Ni 12 P 5 phase (PDF 22-1190) and those around 40.7 • , 44.5 • , 47.3 • and 55.0 • ascribed to Ni 2 P (PDF 03-0953) were detected. This observation showed that low phosphidation temperature favored the formation of Ni 12 P 5 phase [44]. Peaks related to Ni 12 P 5 phase disappeared with the increase of the phosphidation temperature, while the diffraction peaks of Ni 2 P became gradually sharp and strong, indicating the aggregation of the Ni 2 P particle and this result is consistent with TEM images.…”
Section: Morphology and Structure Of Ni 2 P-adc Catalystssupporting
confidence: 83%
See 1 more Smart Citation
“…Compared with other samples, the diffraction peaks of Ni 2 P-528 around 38.4 • , 41.7 • , 46.9 • and 48.9 • corresponding to Ni 12 P 5 phase (PDF 22-1190) and those around 40.7 • , 44.5 • , 47.3 • and 55.0 • ascribed to Ni 2 P (PDF 03-0953) were detected. This observation showed that low phosphidation temperature favored the formation of Ni 12 P 5 phase [44]. Peaks related to Ni 12 P 5 phase disappeared with the increase of the phosphidation temperature, while the diffraction peaks of Ni 2 P became gradually sharp and strong, indicating the aggregation of the Ni 2 P particle and this result is consistent with TEM images.…”
Section: Morphology and Structure Of Ni 2 P-adc Catalystssupporting
confidence: 83%
“…Ni 2 P-578, phosphorized at 578 K, had the highest active site and chemisorbing ability for H 2 which exhibited the highest catalytic activity for isobutane dehydrogenation among these catalysts. For Ni 2 P-528 sample, lower phosphidation temperatures favored the formation of Ni 12 P 5 phase [44], resulting a lower activity and selectivity. Although the particle size of Ni 2 P-553 sample was much smaller due to the lower phosphidation temperature, only small amount of Ni could be phosphorized and thus the catalyst possessed a low density of surface active sites, leading to an inferior catalytic performance.…”
Section: Catalytic Performance For Isobutane Dehydrogenationmentioning
confidence: 99%
“…26 This diffraction peak is in agreement with Brock's observation of the formation of an amorphous Ni-P phase when higher P:Ni stoichiometric ratios are used. 13 In contrast, when ODE is substituted as the solvent, nucleation was not observed until 200-220 ˚C.…”
mentioning
confidence: 99%
“…[9][10][11] The binary Ni-P phase diagram is complex, with a large number of thermodynamically stable stoichiometries (Ni 3 P, Ni 5 P 2 , Ni 12 P 5 , Ni 2 P, Ni 5 P 4 , NiP, NiP 2 , and NiP 3 ), thereby creating a synthetic challenge with respect to accessing phase-pure Ni 2 P. In general, increasing the molar equivalents of phosphide precursor, extending the reaction time, and operating at higher temperatures allow the more phosphorus-rich side of the phase diagram to be accessed for colloidal nanocrystals. [12][13][14] Typical methods used to synthesize high-quality colloidal Ni 2 P nanocrystals use traditional organic solvents (e.g., octadecene (ODE), dioctyl ether), expensive and/or reactive phosphide precursors (tri-n-octylphosphine (TOP), white phosphorus (P 4 ), tris(trimethylsilyl)phosphine (P(TMS) 3 ), and tri-n-butylphosphine), high temperatures, and/or multiple-step reactions. 10,[15][16][17] Triphenylphosphine (PPh 3 ) is a low-cost, less-reactive, and more air-stable phosphide precursor (~15% the cost of TOP in price per mole); 18 however, compared to TOP and P(TMS) 3 , nanocrystals synthesized using PPh 3 are typically large (>45 nm), ill-defined, amorphous, and/or not phase pure.…”
mentioning
confidence: 99%
“…This evidence indicates that the phosphorization process of Ni in an OAm system requires a relatively higher temperature-270 1C-in this work, which is slightly lower than that reported in other work. 30,31 It also indicates that the heterodimer Au-Ni NPs are relatively stable at 230 1C.…”
Section: Growth Mechanismmentioning
confidence: 94%